ECOLOGICAL TOURS AS KEY FOR SUSTAINABLE TOURISM DEVELOPMENT IN TRANSYLVANIA - Gál, Tünde (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2018)
The current society is undergoing a period marked by major changes, caused by global environmental problems and environmental pressures. Therefore, in order to limit the negative impacts of tourism it is necessary to promote tourism forms with low environmental impact, generally known as ecotourism. Romania has a rich ecotourism potential, so the development and promotion of this form of tourism has high capabilities, but some high potential regions, as it is Transylvania, could loose their main attraction – untouched nature – if there is no proper regulation at local level. This paper aims to analyze the current state of eco-touristic sites, with special attention on the differences regarding the impact of the regular and ecological tours on the envirorment, the local community and the local economy. The analysis of the current state of ecological tour supply and demand in the Transylvanian region is based on primary data, identifying on one hand the approach of the tour operators and tour guides towards the organization of ecological tours, on the other hand the perception of the customers towards ecotouristic products. The results indicate that a relative high percentage of the tour operators and tour guides show indifferent attitude towards the organization of ecological tours, even though they are aware of the fact that in order to preserve our natural sites there is need to increase ecological tour offer and the education of the tourists and local community. The customers on the other hand, depending on their socio-economic status and educational level, fall in very different groups when the principles of sustainability are to be kept in practice.